Cost-Effective Micro Programmable Logic Controller for System Automation - Aamir Shahzad,; Qamar ul Islam,; Shaheen Akhtar ,; Mao-Gang He, (Journal of Basic & Applied Sciences, 2013)
The purpose of this study is to check the efficiency of micro programmable logic controller (micro-PLC) for controlling, monitoring and counting purpose of eight different load systems simultaneously. In this project working of different IC’s, Keyboard and seven-segment display were used for visual representation of data for the purpose of simplicity and cost effectiveness and also increases productivity. Complete hardware of the system has been designed, tested and made into working condition. The monitor program takes case of all the necessary requirements of the system like, scanning the keyboard, lighting display, listen the written program and its execution. Microcontroller was programmed in C-language and a flash memory of 2-K bytes was used to store controlled program permanently. This micro-PLC was supportable for monitoring and counting industrial processes and can be implemented in multiple domains, largely of small to medium scale manufacturing processes and may be used for home and business automation as well. The efficiency and simplicity of the micro-PLC are strong advantages, easy to code and allowing fast automation on small systems, making the load switching very effective.